PERANCANGAN ULANG SEKOLAH MENENGAH PERTAMA NEGERI 1 BUMIAYU DENGAN PENDEKATAN PERILAKU - Rizqi, Syahdila Ghifari Alaftha; Rusyda, Rusyda; Rusyda, Hana Faza Surya (eProceedings of Art & Design, 2024)
SMP Negeri 1 Bumiayu is a public school-based junior high school with a total of 947 students and 49 teachers. This school has a very big problem. Much of the comfortable causes students and teachers to feel uncomfortable during teaching and learning activities. This design overcomes the problems that exist in SMP Negeri 1 Bumiayu so that students and teachers feel comfortable when learning and teaching activities and can carry out teaching and learning according to government recommendations, namely full day school. This design includes several rooms that cause inconvenience to users in the room, namely the library, teacher's room, hall room, computer laboratory, canteen and principal's room. The output of the design of Bumiayu 1 Public Middle School is to use a spatial psychology approach, for the theme and concept itself, namely using the concept of contemporary styling. This design uses a spatial Behaviour methodology based on the problems that exist in SMP Negeri 1 Bumiayu. The application of the theme, the concept in this design is based on the existing analysis at SMP Negeri 1 Bumiayu.Keywords: School, Behaviour, Activity, Comfortable